Implications of the Role of Green Jobs in the Development of Low-Carbon Tourism - Angga Wijaya Holman Fasa; Mahardhika Berliandaldo; Muhammad Iqbal Rosyidi; Dini Andriani (Politeknik Pariwisata Makassar, Indonesia, 2024)
Afterward, the tourism sector contributes to environmental impact. Accelerating the tourism sector’s role to achieve net zero carbon tourism activities for a higher quality experience is indispensable. Instead, there is a change in tourism trends that focus on developing sustainable tourism and implementing low carbon tourism within sustainable development, resulting in green job opportunities that positively impact economics, socio cultural, environment, and communities. Based on several previous studies, not much research has been found on the implications of the role of green jobs in developing the tourism sector in Indonesia. Qualitative literature methods such as journals, books, study reports, statistical reports, policy and regulations, and the acquisition of data and information are analyzed using the VRIO (value, rarity, imitability, and organization) approach. This will be done by identifying the issues related to low-carbon tourism and their impact on the value creation of green jobs as an enabler to support sustainable tourism, resource capacity, and competitiveness, as well as the results of the VRIO analysis to obtain strategic implications. Indonesia's low-carbon tourism sector has four key elements that can provide a sustainable competitive advantage: environmental innovation, investment in an environmentally friendly tourism industry, human resource capacity, and green skills.